RESEARCH REVIEW: EMPLOYEE PERFORMANCE RECRUITMENT PROCESS IN HUMAN RESOURCE AND CORPORATE SERVICES SECTION - Adi Lukman Hakim; Ninik Mas'adah; Yulie Wahyuningsih (Jurnal Ekonomi, 2023)
Human resource management is important in achieving goals. In general, company leaders want good performance from their employees in carrying out the tasks assigned by the company. This study aims to determine whether the employee recruitment process on employee performance at PT. Vale Tbk and whether the employee recruitment process on employee performance at PT. Vale Tbk. This study uses quantitative methods by distributing data using questionnaires. The sample in this study are employees at PT. Vale Tbk, the sampling technique used purposive sampling with a total sample of 77 respondents. The data analysis technique used simple linear regression with SPSS 23. The novelty of this research is on the recruitment variable as the independent variable. In addition, the sample objects and targets are in the HR department and corporate services. The results showed that the implementation of employee recruitment has a positive effect on employee performance in the HR and Corporate Services section of PT. Vale Tbk. The results of the analysis of the determinant coefficients show that the employee recruitment implementation variable gives positive results in its implementation with a score of 89.5%, while the remaining 10.5% is influenced by other variables that affect employee performance outside the variables in the study. It implies that recruitment significantly influence towards employee performance.